The relationship between farmers’ entrepreneurial behavior and macroeconomics based on the probit regression model and entrepreneurial psychological capital - Li, Hao; Qi, Na; Li, Zheng; Ma, Wanying (Frontiers in Psychology, 2022)
At present, the research on the influence mechanism of psychological capital on farmers' entrepreneurial behavior is relatively mature. However, the relationship between farmers' entrepreneurial behavior and macroeconomics by entrepreneurial psychological capital (PsyCap) is still unclear. Based on this, firstly, this work analyzes the entrepreneurial PsyCap in detail. Secondly, the research hypothesis is put forward and a conceptual model is implemented. A questionnaire is designed to analyze the current situation of farmers' entrepreneurial PsyCap and entrepreneurial behavior. Finally, a structural equation model (SEM) is implemented to explore the relationship between farmers' entrepreneurial behavior and macroeconomics. The path test of the SEM is utilized to obtain the following. Macroeconomic growth has a significant positive impact on entrepreneurial behavior. Macroeconomics can affect farmers' entrepreneurial behavior to varying degrees by affecting the four entrepreneurial PsyCap of farmers' subjective cognition, Tenacity, hope and open-mindedness. This indicates that entrepreneurial PsyCap plays an intermediary role between farmers' entrepreneurial behavior and macroeconomics. The purpose of this work is to explore the relationship among farmers' entrepreneurial behavior, macroeconomics, and the role of entrepreneurial PsyCap through empirical analysis, thereby providing a theoretical reference for the subsequent country's optimization of farmers' entrepreneurial strategies.